Signal transduction - Gomperts, B. D. (Elsevier/Academic Press, 2009)
Up-to-date, inclusive coverage of targeting transduction pathways for research and medical intervention * In-depth coverage of nuclear receptors, including steps in isolation of steriod hormones and the discovery of intracellular hormone receptors; Tyrosine protein kinases and adaptive immunity; and intracellular calcium * Extensive conceptual colour artwork to assist with comprehension of key topics * Instrumental margin notes highlight milestones in signalling mechanisms DESCRIPTION: Signal Transduction is a thorough, well-illustrated study in cellular signaling processes. Beginning with the basics, this book shows how cells respond to external cues, hormones, growth factors, cytokines, cell surfaces, etc., and further instructs how these inputs are integrated. Instruction continues with up-to-date, inclusive coverage of intracellular calcium, nuclear receptors, tyrosine protein kinases and adaptive immunity, and targeting transduction pathways for research and medical intervention. Signal Transduction serves as an invaluable resource for advanced undergraduates, graduate researchers, and established scientists working in cell biology, pharmacology, immunology, and related fields.